Population genomic, olfactory, dietary, and gut microbiota analyses demonstrate the unique evolutionary trajectory of feral pigs - Simona Petrelli; Maria Buglione; Valeria Maselli; Claudia Troiano; Greger Larson; Laurent Frantz; Aurelie Manin; Ezio Ricca; Loredana Baccigalupi; Dominic Wright; Christian Pietri; Domenico Fulgione (Molecular Ecology, 2022)
Domestication is an intriguing evolutionary process. Many domestic populations are subjected to strong human‐mediated selection, and when some individuals return to the wild, they are again subjected to selective forces associated with new environments. Generally, these feral populations evolve into something different from their wild predecessors and their members typically possess a combination of both wild and human selected traits. Feralisation can manifest in different forms on a spectrum from a wild to a domestic phenotype. This depends on how the rewilded domesticated populations can readapt to natural environments based on how much potential and flexibility the ancestral genome retains after its domestication signature. Whether feralisation leads to the evolution of new traits that do not exist in the wild or to convergence with wild forms, however, remains unclear. To address this question, we performed population genomic, olfactory, dietary, and gut microbiota analyses on different populations of Sus scrofa (wild boar, hybrid, feral and several domestic pig breeds). Porcine single nucleotide polymorphisms (SNPs) analysis shows that the feral population represents a cluster distinctly separate from all others. Its members display signatures of past artificial selection, as demonstrated by values of F ST in specific regions of the genome and bottleneck signature, such as the number and length of runs of homozygosity. Generalised F ST values, reacquired olfactory abilities, diet, and gut microbiota variation show current responses to natural selection. Our results suggest that feral pigs are an independent evolutionary unit which can persist so long as levels of human intervention remain unchanged.

Ancient DNA suggests modern wolves trace their origin to a Late Pleistocene expansion from Beringia - Liisa Loog; Olaf Thalmann; Mikkel‐Holger S. Sinding; Verena J. Schuenemann; Angela Perri; Mietje Germonpré; Herve Bocherens; Kelsey E. Witt; Jose A. Samaniego Castruita; Marcela S. Velasco; Inge K. C. Lundstrøm; Nathan Wales; et al. (Molecular Ecology, 2020)
Grey wolves ( Canis lupus ) are one of the few large terrestrial carnivores that have maintained a wide geographical distribution across the Northern Hemisphere throughout the Pleistocene and Holocene. Recent genetic studies have suggested that, despite this continuous presence, major demographic changes occurred in wolf populations between the Late Pleistocene and early Holocene, and that extant wolves trace their ancestry to a single Late Pleistocene population. Both the geographical origin of this ancestral population and how it became widespread remain unknown. Here, we used a spatially and temporally explicit modelling framework to analyse a data set of 90 modern and 45 ancient mitochondrial wolf genomes from across the Northern Hemisphere, spanning the last 50,000 years. Our results suggest that contemporary wolf populations trace their ancestry to an expansion from Beringia at the end of the Last Glacial Maximum, and that this process was most likely driven by Late Pleistocene ecological fluctuations that occurred across the Northern Hemisphere. This study provides direct ancient genetic evidence that long‐range migration has played an important role in the population history of a large carnivore, and provides insight into how wolves survived the wave of megafaunal extinctions at the end of the last glaciation. Moreover, because Late Pleistocene grey wolves were the likely source from which all modern dogs trace their origins, the demographic history described in this study has fundamental implications for understanding the geographical origin of the dog.

A Dysfunctional Sense of Smell: The Irreversibility of Olfactory Evolution in Free-Living Pigs - Valeria Maselli; Gianluca Polese; Greger Larson; Pasquale Raia; Nicola Forte; Daniela Rippa; Roberto Ligrone; Rosario Vicidomini; Domenico Fulgione (Evolutionary Biology, 2014)

The Balkans and the colonization of Europe: the post‐glacial range expansion of the wild boar, Sus scrofa - Panoraia Alexandri; Alexander Triantafyllidis; Spiros Papakostas; Evangelos Chatzinikos; Petros Platis; Nikolaos Papageorgiou; Greger Larson; Theodore J. Abatzopoulos; Costas Triantaphyllidis (Journal of Biogeography, 2012)
Aim We focus on the biogeographical role of the Balkan Peninsula as a glacial refugium and source of northward post‐glacial dispersal for many European taxa. Specifically, we analysed the genetic structure and variation of wild boar ( Sus scrofa ) samples primarily from Greece, a region that has repeatedly served as a glacial refugium within the Balkan Peninsula. Location Continental Greece, the Aegean island of Samos and Bulgaria. Methods We analysed wild boar samples from 18 localities. Samples from common domestic breeds were also examined to take into account interactions between wild and domesticated animals. Phylogenetic analyses were carried out on a 637‐bp fragment of the mitochondrial DNA control region in 200 wild boar and 27 domestic pigs. The sequences were also compared with 791 Eurasian wild boar and domestic pig D‐loop sequences obtained from GenBank. Results Ninety‐four haplotypes were identified in the European wild boar data set, of which 68 were found in the Balkan samples and assigned to two previously described clades: the E1 European and Near Eastern clades. All of the continental samples clustered in the E1 clade and the samples from Samos fell into the Near Eastern clade, consistent with the island’s proximity to Asia Minor. Intriguingly, 62 novel haplotypes were identified and are found exclusively in the Balkans. Only six haplotypes were shared between wild boar and domestic pigs. Main conclusions Our data reveal numerous novel and geographically restricted haplotypes in wild boar populations, suggesting the presence of separate refugia in the Balkans. Our analyses support the hypothesis of a post‐glacial wild boar expansion consistent with the leading edge model, north and west from modern day Greece, and suggest little maternal introgression of Near Eastern and domestic haplotypes into wild Balkan populations.

Rethinking the evolution of extant sub‐Saharan African suids (Suidae, Artiodactyla) - Jaime Gongora; Rebecca E. Cuddahee; Fabrícia Ferreira do Nascimento; Christopher J. Palgrave; Stewart Lowden; Simon Y. W. Ho; Denbigh Simond; Chandramaya Siska Damayanti; Daniel James White; Wee Tek Tay; Ettore Randi; Hans Klingel; et al. (Zoologica Scripta, 2011)
Gongora, J., Cuddahee, R. E., do Nascimento, F. F., Palgrave, C. J., Lowden, S., Ho, S. Y. W., Simond, D., Damayanti, C. S., White, D. J., Tay, W. T., Randi, E., Klingel, H., Rodrigues‐Zarate, C. J., Allen, K., Moran, C. & Larson, G. (2011). Rethinking the evolution of extant sub‐Saharan African suids (Suidae, Artiodactyla). — Zoologica Scripta, 40 , 327–335. Although African suids have been of scientific interest for over two centuries, their origin, evolution, phylogeography and phylogenetic relationships remain contentious. There has been a long‐running debate concerning the evolution of pigs and hogs (Suidae), particularly regarding the phylogenetic relationships among extant Eurasian and African species of the subfamily Suinae. To investigate these issues, we analysed the mitochondrial and nuclear DNA sequences of extant genera of Suidae from Eurasia and Africa. Molecular phylogenetic analyses revealed that all extant sub‐Saharan African genera form a monophyletic clade separate from Eurasian suid genera, contradicting previous attempts to resolve the Suidae phylogeny. Two major sub‐Saharan African clades were identified, with Hylochoerus and Phacochoerus grouping together as a sister clade to Potamochoerus. In addition, we find that the ancestors of extant African suids may have evolved separately from the ancestors of modern day Sus and Porcula in Eurasia before they colonised Africa. Our results provide a revision of the intergeneric relationships within the family Suidae.